Clinical applications of cardiac computed tomography: a consensus paper of the European Association of Cardiovascular Imaging—part I. (24th January 2022) - Pontone, Gianluca; Rossi, Alexia; Guglielmo, Marco; Dweck, Marc R; Gaemperli, Oliver; Nieman, Koen; Pugliese, Francesca; Maurovich-Horvat, Pal; Gimelli, Alessia; Cosyns, Bernard; Achenbach, Stephan
Abstract: Cardiac computed tomography (CT) was introduced in the late 1990's. Since then, an increasing body of evidence on its clinical applications has rapidly emerged. From an initial emphasis on its technical efficiency and diagnostic accuracy, research around cardiac CT has now evolved towards outcomes-based studies that provide information on prognosis, safety, and cost. Thanks to the strong and compelling data generated by large, randomized control trials, the scientific societies have endorsed cardiac CT as pivotal diagnostic test for the management of appropriately selected patients with acute and chronic coronary syndrome. This consensus document endorsed by the European Association of Cardiovascular Imaging is divided into two parts and aims to provide a summary of the current evidence and to give updated indications on the appropriate use of cardiac CT in different clinical scenarios. This first part focuses on the most established applications of cardiac CT from primary prevention in asymptomatic patients, to the evaluation of patients with chronic coronary syndrome, acute chest pain, and previous coronary revascularization. Graphical Abstract: